Policies are crucial for food system transformation - Swinnen, Johan (Economist Newspaper Limited, 2021)
Food systems hold the key not only to food security, but also to plant, animal and human health, as well as environmental sustainability. The United Nations (UN) will hold its first ever UN Food System Summit in September 2021, since the transformation of food systems is now seen as one of the most impactful approaches to meeting all 17 Sustainable Development Goals.